Inclusive Communication Training through Personal Social Responsibility at SMKN 47 Jakarta - Leila Mona Ganiem; Kholisoh Nur; Nurhayani Saragih; Rachmita Maun Harahap; Muhammad Raqib Mohd Sofian (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
This International Joint Community Service (KLN) program aimed to improve inclusive communication competence among vocational students by addressing communication barriers between the hearing majority and Deaf/Hard-of-Hearing (HoH) communities. Conducted collaboratively by Universitas Mercu Buana and Universiti Sains Islam Malaysia at SMK Negeri 47 Jakarta, the program involved 14 students through participatory and competency-based training activities. The intervention was grounded in Personal Social Responsibility (PSR) and Shared Labor frameworks. Training activities included Deaf culture awareness, Communication Repair strategies, Total Communication principles, BISINDO practice, simulations, and reflective discussions. Evaluation results showed a 53% increase in understanding of Deaf culture, a 63% increase in basic BISINDO knowledge, a 55% increase in Communication Repair skills, and a 45% increase in communication confidence. Participants also proposed simple accessibility adaptations relevant to vocational contexts. The findings indicate that PSR-based inclusive communication training can strengthen ethical awareness, communication competence, and social inclusion in vocational education.